Evaluation of a digital health system (PAHcare™) for routine care of patients with pulmonary arterial hypertension: The CBS-PAH study protocol - Pérez Peñate, Gregorio; Ochoa Parra, Nuria; Domingo Morera, Juan Antonio; Martínez Meñaca, Amaya; López Ramón, Marta; Cadenas Menéndez, Sergio; León Marrero, Fernando; Gómara de la Cal, Sara; Ghadban Garrido, Cristina; Royo Tolosana, Patricia; Martin Puentes, Javier; Aldonza Aguayo, Rebeca; et al. (Frontiers in Public Health, 2022)
Introduction Pulmonary arterial hypertension (PAH) is a rare, multifactorial, chronic condition that requires ongoing monitoring and assessment. PAHcare™ is a novel, patient-centered digital platform that provides software intended for use on patients’ mobile phones (downloadable application) and web-based dashboards for use by physicians and health coaches (HC). We describe herein the clinical investigation plan of a clinical study aimed at evaluating the clinical benefit and safety of PAHcare™ for the routine management of patients with PAH. Methods and Analysis In this prospective, single cohort, multicenter study, 50 patients with PAH will be recruited at six specialized PAH units from reference hospitals of the public Spanish healthcare system. The PAHcare™ digital health platform allows patients to log health and lifestyle information while also providing structured content for patient education, medication reminders, and behavioral and lifestyle coaching from a remote HC. Evaluation will be primarily focused on the impact of the platform use on the patient’s health-related quality of life (HRQoL) via questionnaires completion through electronic patient-reported outcomes. Moreover, the analysis of the impact on the patient’s functional status, signs and symptoms of PAH, patient costs and healthcare resource utilization, satisfaction, knowledge of the disease and its management, and adherence to and safety of the platform will be secondary outcomes. The clinical investigation started in July 2021 and is expected to end by September 2022. Discussion The PAHcare™ platform is anticipated to provide direct benefits to healthcare professionals, patients, and caregivers. These include the simplification of the multidisciplinary approach needed to tailor routine PAH management, enhancement of the patient/healthcare professional interaction, patient’s empowerment to become more actively involved in the management and treatment of the disease, and increase of the patient’s and caregiver’s knowledge on PAH. Ethics and Dissemination The competing Ethics Committee of the Hospital 12 de Octubre, Madrid, Spain, approved the study protocol V3.0 January 14, 2022 (FPAH-CI-2101); the clinical investigation was registered at the NEOPS database for clinical investigation studies with medical devices approved in the EU of the Spanish Agency of Medicines and Medical Devices (AEMPS; https://neops.aemps.es/neops/login) on the 6 June 2021 (registry number 21-0050).